Analisis Teori Tindakan Sosial Max Weber dan Teori Fakta Sosial Emile Durkheim dalam Pengenalan Tradisi Lokal Kemasyarakatan - Miftahul Fikria; Agoes Moh. Moefad (An-Nuha : Jurnal Kajian Islam, Pendidikan, Budaya dan Sosial, 2024)
This article discusses Max Weber's theory of social action and Emil Durkheim's theory of social facts in the introduction of local community traditions. This article aims to find the existence of Max Weber's social action theory and Emile Durkheim's social fact theory in the introduction of local community traditions. This research uses a qualitative approach, with the type of library research that uses descriptive-analytical data analysis techniques. The results of the discussion in this article are that when viewed from Max Weber's theory of social facts, namely traditional actions, affective actions and social actions, the introduction of traditions is based on habits that have been rooted for generations, then the introduction of traditions is carried out on the basis of feelings and emotions (unconscious). In addition, the introduction of tradition is carried out by someone based on conscious consideration and choice, so the aim is to introduce the region, usually this is done by government agencies. Meanwhile, based on Emile Durkhim's social action theory, namely material and non-material forms, in the introduction of tradition there must be a fact that can be seen directly or observed and the introduction of tradition is a form of expression of one's feelings towards the traditions that have prevailed.